Reliable And Practical Guidelines For Planning An Effective English Lesson. - Solís Hernández, Mayra (2012)
The aim of this article is to help student teachers develop their planning skills and to provide insight into lesson preparation. This article presents reliable and practical guidelines to prepare effective English lessons. These basic principles have arisen from my seven-year experience teaching the practicum for the Master's program in Teaching English as a Foreign Language at the University of Costa Rica. A lesson plan format is also suggested as a useful tool for both trainees and teacher trainers in the field of English teaching. This template has proven to be very useful during the Practicum and has been highly recommended by the trainees in this program.